Программная реализация выделения зон интереса на термограммах различного радиоэлектронного оборудования - Гарячевская, Д. В. (ХНУРЭ, 2012)
Thermograph y method allows to obtain images(thermograms) of various equipment. The main objective of this project is to develop software to match the visible image and thermogram. To do this it is necessary perform certain stages of preparation of the visible image and thermogram with further comparison.
Keywords: термограмма; радиоэлектронное оборудование